Metacognitive Interpersonal Mindfulness-Based Training for Worry About Interpersonal Events: A Pilot Feasibility and Acceptability Study. Issue 11 (November 2019) - Ottavi, Paolo; Passarella, Tiziana; Pasinetti, Manuela; MacBeth, Angus; Velotti, Patrizia; Velotti, Anna; Bandiera, Aldea; Popolo, Raffaele; Salvatore, Giampaolo; Dimaggio, Giancarlo
Abstract : Abstract: Individuals with personality disorders experience worry and repetitive thoughts regarding interpersonal scenarios. Mainstream mindfulness-based approaches may be insufficient to soothe these individual's distress due to difficulties in letting thoughts go and refocusing attention to the present moment. For this reason, we devised an adapted form of mindfulness-based program called Metacognitive Interpersonal Mindfulness-Based Training (MIMBT) for personality disorders. In this pilot study, 28 individuals attended nine weekly sessions to evaluate the feasibility and acceptability, and to establish preliminary outcomes. All individuals completed the program. Attendance was very high (96%). Significant changes were observed on the primary outcome of reduction in repetitive thinking, measured using the Metacognition Questionnaire-30. We also observed a decrease in depression severity. Despite important limitations, this pilot study suggests that MIMBT has the potential to be a viable and well-accepted option for increasing positive outcomes in the treatment of personality disorders. Clinical considerations and directions for future research are discussed.